Preparation method and application of a degradable polyepoxy chain extender

The degradable polyepoxy chain extender prepared by solution polymerization solves the problem that the existing non-degradable chain extender affects the degradation performance of the material, and realizes effective chain extension of the polymer material while ensuring the biodegradation performance.

CN116655848BActive Publication Date: 2025-03-18ANHUI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310588738.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-03-18
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

The use of existing non-degradable polyepoxy chain extenders in degradable polymer materials will affect their degradability performance, and the preparation methods of existing degradable chain extenders are complex and difficult to be produced on a large scale.

Method used

The degradable polyepoxy chain extender obtained by reaction of vinyl monomer, acid ester monomer and glyceryl acrylate monomer was prepared by solution polymerization. By controlling the reaction conditions and the molar ratio of monomers, a chain extender with controllable molecular weight and good biodegradation performance was obtained.

Benefits of technology

It achieves good chain expansion effect on polymer materials at low addition amounts, while ensuring the biodegradation performance of the material. The preparation process is simple, the chain extender structure can be designed, and the epoxy value can be adjusted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116655848B_ABST
    Figure CN116655848B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a degradable polyepoxy chain extender. The structural formula of the chain extender is as follows: the invention adopts solution polymerization to obtain a copolymer with controllable molecular weight and narrow molecular weight distribution, and the polymerization process reduces the hydrolysis of epoxy groups in glycidyl methacrylate, improves the reaction activity of the chain extender, and can achieve a good chain extension effect of the polymer material at a low addition amount; and the main chain of the chain extender contains an ester group, has good biodegradability in acidic, alkaline or microbial environments, and is applied to degradable plastics without affecting their degradation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable polymer materials, and in particular relates to a preparation method and application of a degradable polyepoxy chain extender (SHG). Background Art

[0002] With the continuous strengthening of environmental protection awareness and the deepening of the concept of sustainable development, people have gradually increased their research on environmentally friendly materials, and the research on biodegradable polymer materials has always been one of the important directions in this field. At present, polylactic acid (PLA) and polybutylene adipate terephthalate (PBAT) are two common biodegradable materials. PLA can be made by condensation of lactic acid produced by fermentation of corn, corn stalks, sugarcane, cassava, etc. It has good biological origin and can be completely biodegraded, but its defects such as high brittleness and slow biodegradation rate limit its application in packaging materials, disposable plastic products and films; PBAT has the advantages of good toughness and fast biodegradation rate, but its strength is low and its gloss is poor. The composite system made of PLA and PBAT can make the two complement each other's advantages and learn from each other's strengths.

[0003] However, the solubility parameters of PLA and PBAT are quite different, and they are typical incompatible systems. The performance of the blends obtained by simple melt blending is poor. In order to improve the comprehensive performance of PLA / PBAT blends, it is necessary to introduce a chain extender during the blending process to reduce the interfacial tension between PLA and PBAT and enhance the adhesion of the interface, so as to achieve the purpose of improving the compatibility of the two-phase system. The most common chain extender at present is a polyepoxy polymer, such as patents CN102936307, CN112778454A, etc., which disclose chain extenders prepared from styrene monomers and glyceryl acrylate monomers as raw materials. The principle of its volume expansion is that the epoxy group in the chain extender reacts with the hydroxyl or carboxyl group at the end of PLA and PBAT to form a grafted polymer, so that the polymer molecular weight increases, the interfacial bonding force of the two phases increases, and the compatibility is improved. However, this type of chain extender is non-degradable, and its application in degradable polymer materials will affect its degradation performance. Patent CN112279985A discloses the synthesis of a degradable chain extender using cycloketone acetal and glycidyl methacrylate by RAFT polymerization, but this synthesis method is relatively complicated and not easy to mass produce. Therefore, how to ensure the chain extension and capacity-enhancing effect of the chain extender on degradable plastics such as PLA and PBAT, and how to make the preparation process simple and have its own biodegradability has important theoretical value and practical significance for the promotion and use of degradable plastics. Summary of the invention

[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a preparation method and application of a degradable polyepoxy chain extender (SHG).

[0005] In order to achieve the purpose, the present invention adopts the following technical scheme:

[0006] A degradable polyepoxy chain extender (SHG) is represented by the following structural formula as shown in formula (1):

[0007]

[0008] Among them, n1, n2, n3 are the degrees of polymerization, and n1, n2, n3 are all between 30-500.

[0009] The degradable polyepoxy chain extender of the present invention is obtained by reacting three types of monomers, wherein the first type of monomer is a vinyl monomer, the second type of monomer is an acid ester monomer, and the third type of monomer is an acrylic glycerol ester monomer, and the molar ratio of the first type of monomer, the second type of monomer and the third type of monomer is 100-150:10-50:80-180.

[0010] Preferably, the vinyl monomer is one or more of styrene, acrylonitrile and methyl styrene. The acid ester monomer is one or more of 1,6-hexanediol diacrylate, 1,5-pentanediol diacrylate and 1,3-butanediol diacrylate. The glyceryl acrylate monomer is one or more of glycidyl methacrylate and glycidyl methacrylate ether.

[0011] Preferably, a solvent, an initiator and a chain transfer agent are also added to the reaction of the three types of monomers; the solvent is selected from one of toluene and tetrahydrofuran; the initiator is selected from one of azobisisobutyronitrile and benzoyl peroxide, and the amount of the initiator is 1-5wt% of the total mass of the monomers; the chain transfer agent is selected from one or a combination of sodium dodecyl sulfate, 1,1,2,2-tetrachloroethane, 2,4-diphenyl-4-methyl-1-pentene, and the amount of the chain transfer agent is 1-5wt% of the total mass of the monomers.

[0012] The preparation method of the degradable polyepoxy chain extender of the present invention comprises the following steps:

[0013] Step 1, add the solvent into a four-necked flask, introduce nitrogen to keep the reaction system under anaerobic conditions, turn on constant temperature heating and mechanical stirring, control the temperature between 65-85°C, and control the stirring rate between 150-200rpm;

[0014] Step 2, the three types of monomers, initiator, and chain transfer agent are mixed uniformly according to the ratio, and added dropwise to the solvent under mechanical stirring and nitrogen atmosphere at a dropping rate of 20-40 drops / min. After the dropping is completed, the reaction is continued at a constant temperature for 2-8 hours to obtain a polymerization solution;

[0015] Step 3: Add the polymerization solution dropwise to the ethanol solution to obtain a flocculent product, wash it with ethanol and acetone in sequence, and then place it in a vacuum oven at 40-60° C. for 10-20 hours to obtain a powdered degradable polyepoxy chain extender.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0017] 1) The present invention adopts solution polymerization to obtain a copolymer with controllable molecular weight and narrow molecular weight distribution, and the polymerization process reduces the hydrolysis of epoxy groups in glycidyl methacrylate, improves the reaction activity of the chain extender, and can achieve a good chain extension effect of the polymer material at a low addition amount; and the main chain of the chain extender contains an ester group, has good biodegradability in acidic, alkaline or microbial environments, and is applied to degradable plastics without affecting their degradation performance.

[0018] 2) The preparation method of the degradable polyepoxy chain extender (SHG) of the present invention is simple, the chain extender structure can be designed, and the epoxy value can be adjusted.

[0019] 3) The chain extender provided by the present invention has a wide range of uses, and has a significant chain extension effect on polymer materials such as polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polyhydroxyalkanoate (PHA), polybutylene succinate adipate (PBSA), and polycaprolactone (PCL).

[0020] 4) The present invention optimizes various process conditions to obtain high reaction yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the Fourier transform infrared spectrum (FTIR) of the degradable polyepoxy chain extender (SHG) obtained in Example 1;

[0022] Figure 2 The hydrogen nuclear magnetic resonance spectrum of the degradable polyepoxy chain extender (SHG) obtained in Example 1 ( 1 H-NMR);

[0023] Figure 3 The differential scanning calorimetry (DSC) diagram of the degradable polyepoxy chain extender (SHG) obtained in Example 1;

[0024] Figure 4 This is the thermogravimetric analysis chart (TG) of the degradable polyepoxy chain extender (SHG) obtained in Example 1. DETAILED DESCRIPTION

[0025] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0026] In the following examples: styrene, 1,6-hexanediol diacrylate, glycidyl methacrylate, azobisisobutyronitrile, 2,4-diphenyl-4-methyl-1-pentene were all purchased from Adamas. PLA was purchased from NatureWorks, model 2003D; PBAT was purchased from Xinjiang Lanshan Tunhe Polyester Company, model TH801T. ADR chain extender was purchased from BASF, model 4468; KL-E chain extender was purchased from Shanxi Chemical Research Institute.

[0027] Example 1

[0028] A method for preparing a degradable polyepoxy chain extender (SHG) comprises the following steps:

[0029] (1) 180 mL of toluene solvent was added to a four-necked flask, nitrogen was introduced to keep the reaction system under anaerobic conditions, and the mixture was heated to 75° C. and mechanical stirring was started at a stirring rate of 180 rpm.

[0030] (2) 8.3 g of styrene, 7.2 g of 1,6-hexanediol diacrylate, 20.2 g of glycidyl methacrylate, 1.7 g of azobisisobutyronitrile, and 1.7 g of 2,4-diphenyl-4-methyl-1-pentene were weighed in sequence, mixed and dissolved uniformly, and then slowly added dropwise to a four-necked flask using a dropping funnel. After the addition was completed, the reaction was continued at 75° C. for 6 hours to obtain a polymerization solution.

[0031] (3) The polymerization solution was added dropwise to an ethanol solution to obtain a flocculent product, which was washed three times with ethanol and acetone in sequence to purify the product, and then placed in a vacuum oven at 50° C. for 12 h to obtain a powdered biodegradable polyepoxy chain extender (SHG).

[0032] The product was structurally analyzed by Fourier transform infrared spectroscopy and nuclear magnetic resonance hydrogen spectroscopy. Figure 1 and 2 . In the infrared spectrum: 1493cm -1 、1600cm -1 1728cm is the vibration peak of the benzene ring skeleton, corresponding to the styrene structural unit in SHG; -1 is the stretching vibration peak of the carbonyl group, and at 1100 cm -1 There is a strong absorption peak of COC at 906 cm-1, corresponding to the structural unit of 1,6-hexanediol diacrylate; -1It is the characteristic peak of the epoxy group, corresponding to the glycidyl methacrylate structural unit. At the same time, in the hydrogen nuclear magnetic resonance spectrum: δ = 7.28ppm is the proton peak on the benzene ring, corresponding to the styrene structural unit; δ = 2.29ppm is the proton peak of -CH2- connected to the carbonyl group, corresponding to the 1,6-hexanediol diacrylate structural unit; δ = 2.58ppm and δ = 2.77ppm are the proton peaks of -CH2- in the epoxy group, and δ = 3.11ppm is the proton peak of -CH- in the epoxy group, corresponding to the glycidyl methacrylate structural unit in the copolymer, indicating that the product was successfully synthesized. See the attached differential scanning calorimetry diagram Figure 3 The theoretical glass transition temperature (Tg) of the product is 56.47°C, and the tested Tg is 57.34°C, which is close to the theoretical calculated value. Figure 4 The 5% thermal weight loss temperature of the product is 277.67℃, which meets the processing temperature requirements of most biodegradable plastics.

[0033] 0.6wt% of SHG of Example 1, 30wt% of PLA and 70wt% of PBAT were mixed and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0034] Example 2

[0035] A method for preparing a degradable polyepoxy chain extender (SHG) comprises the following steps:

[0036] (1) 180 mL of toluene solvent was added to a four-necked flask, nitrogen was introduced to keep the reaction system under anaerobic conditions, and the mixture was heated to 75° C. and mechanical stirring was started at a stirring rate of 180 rpm.

[0037] (2) 8.3 g of styrene, 7.2 g of 1,6-hexanediol diacrylate, 20.2 g of glycidyl methacrylate, 1.7 g of azobisisobutyronitrile, and 0.4 g of 2,4-diphenyl-4-methyl-1-pentene were weighed in sequence, mixed and dissolved uniformly, and then slowly added dropwise to a four-necked flask using a dropping funnel, and reacted at 75° C. for 6 hours to obtain a polymerization solution.

[0038] (3) The polymerization solution was added dropwise to an ethanol solution to obtain a flocculent product, which was washed three times with ethanol and acetone in sequence to purify the product, and then placed in a vacuum oven at 50° C. for 12 h to obtain a powdered biodegradable polyepoxy chain extender (SHG).

[0039] 0.6wt% of SHG of Example 2, 30wt% of PLA and 70wt% of PBAT were mixed and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0040] Example 3

[0041] A method for preparing a degradable polyepoxy chain extender (SHG) comprises the following steps:

[0042] (1) 150 mL of toluene solvent was added to a four-necked flask, nitrogen was introduced to keep the reaction system under anaerobic conditions, and the mixture was heated to 75° C. and mechanical stirring was started at a stirring rate of 180 rpm.

[0043] (2) 8.3 g of styrene, 7.2 g of 1,6-hexanediol diacrylate, 13.6 g of glycidyl methacrylate, 1.4 g of azobisisobutyronitrile, and 0.3 g of 2,4-diphenyl-4-methyl-1-pentene were weighed in sequence, mixed and dissolved uniformly, and then slowly added dropwise to a four-necked flask using a dropping funnel, and reacted at 75° C. for 5 hours to obtain a polymerization solution.

[0044] (3) The polymerization solution was added dropwise to an ethanol solution to obtain a flocculent product, which was washed three times with ethanol and acetone in sequence to purify the product, and then placed in a vacuum oven at 50° C. for 12 h to obtain a powdered biodegradable polyepoxy chain extender (SHG).

[0045] 0.6wt% of SHG of Example 3, 30wt% of PLA and 70wt% of PBAT were mixed and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0046] Example 4

[0047] A method for preparing a degradable polyepoxy chain extender (SHG) comprises the following steps:

[0048] (1) 120 mL of toluene solvent was added to a four-necked flask, nitrogen was introduced to keep the reaction system under anaerobic conditions, and the mixture was heated to 75° C. and mechanical stirring was started at a stirring rate of 180 rpm.

[0049] (2) 8.3 g of styrene, 5.4 g of 1,6-hexanediol diacrylate, 11.4 g of glycidyl methacrylate, 1.2 g of azobisisobutyronitrile, and 1.0 g of 2,4-diphenyl-4-methyl-1-pentene were weighed in sequence, mixed and dissolved uniformly, and then slowly added dropwise to a four-necked flask using a dropping funnel, and reacted at 75° C. for 6 hours to obtain a polymerization solution.

[0050] (3) The polymerization solution was added dropwise to an ethanol solution to obtain a flocculent product, which was washed three times with ethanol and acetone in sequence to purify the product, and then placed in a vacuum oven at 50° C. for 12 h to obtain a powdered biodegradable polyepoxy chain extender (SHG).

[0051] 0.6wt% of SHG of Example 4, 30wt% of PLA and 70wt% of PBAT were mixed and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0052] Example 5

[0053] A method for preparing a degradable polyepoxy chain extender (SHG) comprises the following steps:

[0054] (1) 150 mL of toluene solvent was added to a four-necked flask, nitrogen was introduced to keep the reaction system under anaerobic conditions, and the mixture was heated to 75° C. and mechanical stirring was started at a stirring rate of 180 rpm.

[0055] (2) 8.3 g of styrene, 1.9 g of 1,6-hexanediol diacrylate, 11.4 g of glycidyl methacrylate, 1.0 g of azobisisobutyronitrile, and 0.3 g of sodium dodecyl sulfate were weighed in sequence, mixed and dissolved uniformly, and then slowly added dropwise to a four-necked flask using a dropping funnel, and reacted at 75° C. for 6 hours to obtain a polymerization solution.

[0056] (3) The polymerization solution was added dropwise to an ethanol solution to obtain a flocculent product, which was washed three times with ethanol and acetone in sequence to purify the product, and then placed in a vacuum oven at 50° C. for 12 h to obtain a powdered biodegradable polyepoxy chain extender (SHG).

[0057] 0.6wt% of SHG of Example 5, 30wt% of PLA and 70wt% of PBAT were mixed evenly and placed in a torque rheometer for internal kneading at a temperature of 180°C, a rotation speed of 50rpm and a time of 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at a temperature of 190°C to form a 100×10×2mm 3The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0058] Example 6

[0059] The degradation experiment of the degradable polyepoxy chain extender (SHG) in Examples 1-5 is specifically performed as follows:

[0060] 1) Add SHG to tetrahydrofuran at a mass concentration of 5 wt% to completely dissolve it, pour it into a mold and dry it to make a 10×20×0.1 mm 3 The size was placed in a vacuum dryer at 50℃ for 12 hours and its mass was weighed W0.

[0061] 2) The prepared sample was placed in a PBS buffer solution with a pH of 7.4, 0.5 wt% lipase was added, and the solution was placed in a 37°C constant temperature shaker. The sample was taken out every 48 hours, washed with ethanol, and placed in a 50°C vacuum dryer for 12 hours. The sample was weighed W, and the residual weight rate was calculated as (W / W0)×100%.

[0062] The degradation residual weight rate after 10 days is shown in Table 1.

[0063] Comparative Example 1

[0064] 30wt% PLA and 70wt% PBAT were mixed evenly and placed in a torque rheometer for internal kneading at 180°C, 50rpm, and 600s. The internal kneaded sample was hot-pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0065] Comparative Example 2

[0066] 0.6wt% commercially available ADR chain extender, 30wt% PLA and 70wt% PBAT were mixed evenly and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3 The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0067] Comparative Example 3

[0068] 0.6wt% of commercial KL-E chain extender, 30wt% of PLA and 70wt% of PBAT were mixed evenly and placed in a torque rheometer for internal kneading at 180°C, 50rpm and 600s. The internal kneaded sample was hot pressed using a flat vulcanizer for 300min at 190°C to form a 100×10×2mm 3The tensile properties of the large and small specimens were tested, and the test results are shown in Table 1.

[0069] Performance Testing

[0070] The molecular weight, mechanical properties and degradation properties of Examples 1-5 and Comparative Examples 1-3 were tested. The results are shown in Table 1.

[0071] As can be seen from Table 1, the molecular weight of SHG in Examples 1-5 changes with the change of reaction conditions, indicating that SHG is a chain extender with controllable molecular weight.

[0072] As can be seen from Table 1, after adding 0.6wt% of SHG in Examples 1-5, the mechanical properties of the PLA / PBAT composite material have been significantly improved. In Comparative Example 1, the tensile strength of the pure PLA / PBAT sample is 8.92MPa, and the elongation at break is 342.92%; after adding SHG chain extension in Example 1, the tensile strength is increased to 12.98MPa, and the elongation at break is increased to 994.88%, which are 45.52% and 190.12% higher than the pure sample, respectively. Compared with Comparative Examples 2 and 3, the addition of SHG improves the tensile properties of the composite material more significantly.

[0073] As can be seen from Table 1, compared with Comparative Examples 2 and 3, the weight of Examples 1-5 decreased significantly after being placed in the enzyme solution for 10 days, indicating that SHG has good biodegradability.

[0074] Table 1 Performance test results

[0075]

[0076] Finally, it should be noted that the above is only a preferred embodiment of the present invention and not a limitation on the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A degradable polyepoxy chain extender, characterized in that: The degradable polyepoxy chain extender is obtained by reacting three types of monomers, wherein the first type of monomer is styrene, the second type of monomer is 1,6-hexanediol diacrylate, and the third type of monomer is glycidyl methacrylate, and the molar ratio of the first type of monomer, the second type of monomer and the third type of monomer is 100-150:10-50:80-180; the preparation method of the degradable polyepoxy chain extender comprises the following steps: Step 1, adding a solvent into a four-necked flask, introducing nitrogen to keep the reaction system under anaerobic conditions, and turning on constant temperature heating and mechanical stirring, the temperature is controlled between 65-85°C, and the stirring rate is controlled at 150-200 rpm; the solvent is selected from one of toluene and tetrahydrofuran; Step 2, the three types of monomers, initiator, and chain transfer agent are mixed uniformly according to a ratio, and are added dropwise to the solvent under mechanical stirring and nitrogen atmosphere. After the addition is completed, the reaction is continued at a constant temperature for 2-8 hours to obtain a polymerization solution; the initiator is selected from one of azobisisobutyronitrile and benzoyl peroxide, and the amount of the initiator is 1-5 wt% of the total mass of the monomers; the chain transfer agent is 2,4-diphenyl-4-methyl-1-pentene, and the amount of the chain transfer agent is 1-5 wt% of the total mass of the monomers; Step 3: Add the polymerization solution dropwise into ethanol to obtain a flocculent product, wash it with ethanol and acetone in sequence, and then bake it in a vacuum oven at 40-60° C. for 10-20 h to obtain a powdered degradable polyepoxy chain extender.

2. An application of the degradable polyepoxy chain extender according to claim 1, characterized in that: The degradable polyepoxy chain extender can be used to increase the molecular weight of polymer materials.

3. The use according to claim 2, characterized in that: The polymer material is polylactic acid, polybutylene adipate-terephthalate, polybutylene succinate, polyhydroxyalkanoate, polybutylene succinate-adipate or polycaprolactone.

Citation Information

Patent Citations

  • Degradable chain extender as well as preparation method and application thereof

    CN112279985A

  • Polyepoxy chain extender as well as preparation method and application thereof

    CN112778454A

  • Chain-expanding agent

    CN101338043A

  • Preparation method and application of comb-type epoxy capacity-increasing chain extender for polymer material

    CN103881001A